Gut microbiota markers in early childhood are linked to farm living, pets in household and allergy. - Annika Ljung; Monica Gio-Batta; Bill Hesselmar; Henrik Imberg; Hardis Rabe; Forough L Nowrouzian; Susanne Johansen; Carl-Johan Törnhage; Gunhild Lindhagen; Margareta Ceder; Anna-Carin Lundell; Anna Rudin; et al. (PLoS ONE, 2024)
Background Children growing up on farms or with pets have a lower risk of developing allergy, which may be linked to their gut microbiota development during infancy. Methods Children from the FARMFLORA birth cohort (N = 65), of whom 28 (43%) lived on a dairy farm and 40 (62%) had pets, provided fecal samples at intervals from 3 days to 18 months of age. Gut microbiota composition was characterized using quantitative microbial culture of various typical anaerobic and facultatively anaerobic bacteria, with colonization rate and population counts of bacterial groups determined at the genus or species level. Allergy was diagnosed at three and eight years of age by experienced pediatricians. Generalized estimating equations were used to identify associations between farm residence or pet ownership, gut microbiota development and allergy. Adjustments were made for important potential confounders. Results Growing up on a farm was associated with a higher ratio of anaerobic to facultative bacteria in the first week, smaller Escherichia coli populations in colonized children in the first months of life and less frequent colonization by Clostridioides difficile at 12 months of age. Having pets in the household was associated with more frequent colonization by Bifidobacterium, Lactobacillus and Bacteroides in the first months. A higher ratio of anaerobic to facultative bacteria at one week of age, early colonization by Bifidobacterium, Lactobacillus and Bacteroides, and reduced carriage of C. difficile at 4-12 months of age all correlated negatively with subsequent allergy diagnosis. Conclusions Our findings indicate that lower rates of allergy in children growing up on farms or with pets may be related to early establishment of typical anaerobic commensals in their gut microbiota. However, further studies are needed to validate our observations in this small birth cohort study.